2018
DOI: 10.1158/1078-0432.ccr-17-3364
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Gastric Cancer with Novel Methylated DNA Markers: Discovery, Tissue Validation, and Pilot Testing in Plasma

Abstract: Gastric adenocarcinoma is the third most common cause of cancer mortality worldwide. Accurate and affordable noninvasive detection methods have potential value for screening and surveillance. Herein, we identify novel methylated DNA markers (MDM) for gastric adenocarcinoma, validate their discrimination for gastric adenocarcinoma in tissues from geographically separate cohorts, explore marker acquisition through the oncogenic cascade, and describe distributions of candidate MDMs in plasma from gastric adenocar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Aging, diet, obesity, H. pylori and Epstein Barr virus infection are all associated with gene methylation in GC [15]. Studies confirmed the involvement of DNA methylation in the transformation of the normal gastric mucosa to GC [16]. The tumor-related genes are hypermethylated in precancerous lesions and intestinal metaplasia [17,18], and inhibiting DNA methylation reduces the incidence of GC in animal models [19,20], DNA methylation could be used as a biomarker for diagnosis, treatment and prognosis of GC [15,21].…”
Section: Introductionmentioning
confidence: 82%
“…Aging, diet, obesity, H. pylori and Epstein Barr virus infection are all associated with gene methylation in GC [15]. Studies confirmed the involvement of DNA methylation in the transformation of the normal gastric mucosa to GC [16]. The tumor-related genes are hypermethylated in precancerous lesions and intestinal metaplasia [17,18], and inhibiting DNA methylation reduces the incidence of GC in animal models [19,20], DNA methylation could be used as a biomarker for diagnosis, treatment and prognosis of GC [15,21].…”
Section: Introductionmentioning
confidence: 82%
“…Interestingly, we showed that ZNF569me levels could discriminate between ECa and normal esophagus with high speci city, regardless of the histotype, con rming and extending those previous reports. Furthermore, ZNF569me was shown to play a tumor suppressive role in head and neck squamous cell carcinoma (29) and a DNA-methylation based panel, which included ZNF569, discriminated gastric adenocarcinoma from normal mucosa (30).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we showed that ZNF569me levels could discriminate between ECa and normal esophagus with high speci city, regardless of the histotype, extending those previous reports. Furthermore, ZNF569me was shown to play a tumor-suppressive role in head and neck squamous cell carcinoma (36) and a DNA-methylation based panel, which included ZNF569me, discriminated gastric adenocarcinoma from normal mucosa (37).…”
Section: Discussionmentioning
confidence: 99%